MRI Brain Activation During Instruction of Dyslexic Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Ten children with dyslexia and 11 normal readers performed tasks of phoneme mapping (assigning sounds to letters) and morpheme mapping (relating suffixed words to their roots) during fMRI scanning, before and after 28 hours of comprehensive reading instruction, in a study of the effects of reading instruction on brain activation in children with dyslexia at University of Washington, Seattle, WA.